2023
DOI: 10.1021/acs.jctc.3c00693
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Intramolecular Basis Set Superposition Errors

Quentin Pitteloud,
Peter Wind,
Stig Rune Jensen
et al.

Abstract: We show that medium-sized Gaussian basis sets lead to significant intramolecular basis set superposition errors at Hartree–Fock and density functional levels of theory, with artificial stabilization of compact over extended conformations for a 186 atom deca-peptide. Errors of ∼80 and ∼10 kJ/mol are observed, with polarized double zeta and polarized triple zeta quality basis sets, respectively. Two different procedures for taking the basis set superposition error into account are tested. While both reduce the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 65 publications
(97 reference statements)
0
5
0
Order By: Relevance
“…25 We have recently quantified intramolecular BSSE for a 186-atom peptide and shown that quadruple-ζ quality basis sets are required to reduce the BSSE to below 1 kJ/ mol with Hartree−Fock (HF) and density functional theory (DFT) methods. 29 Although an overestimation of the attractive interaction energy is the most commonly observed effect, Mentel for the Be dimer is underestimated by medium-sized basis sets and that the CP correction here leads to an even larger underestimation. 30 A similar observation has been made by Alvarez-Idaboy and Galano for the Ar dimer.…”
Section: ■ Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…25 We have recently quantified intramolecular BSSE for a 186-atom peptide and shown that quadruple-ζ quality basis sets are required to reduce the BSSE to below 1 kJ/ mol with Hartree−Fock (HF) and density functional theory (DFT) methods. 29 Although an overestimation of the attractive interaction energy is the most commonly observed effect, Mentel for the Be dimer is underestimated by medium-sized basis sets and that the CP correction here leads to an even larger underestimation. 30 A similar observation has been made by Alvarez-Idaboy and Galano for the Ar dimer.…”
Section: ■ Introductionmentioning
confidence: 86%
“…A valence bond approach can be used to estimate intramolecular BSSE but cannot account for charge-transfer effects . We have recently quantified intramolecular BSSE for a 186-atom peptide and shown that quadruple-ζ quality basis sets are required to reduce the BSSE to below 1 kJ/mol with Hartree–Fock (HF) and density functional theory (DFT) methods …”
Section: Introductionmentioning
confidence: 99%
“…The resulting representations, denoted f_n and df_n, are fully described by their mathematical definitions in Eqs. (7) and (9), respectively. 42 Figures 2 and 3 In Fig.…”
Section: Scaling and Wavelet Projectors In Vampyrmentioning
confidence: 99%
“…In particular, multiwavelets have recently been employed within the field of quantum chemistry to overcome some of the known drawbacks of traditional atomic orbital (AO)-based calculations. [1][2][3][4][5][6][7][8][9] The code that pioneered this approach is M-A-D-N-E-S-S, 10 followed by our own code, MRChem. 11 To date, they are the only two codes available for quantum chemistry calculations using multiwavelets.…”
Section: Introductionmentioning
confidence: 99%
“…MRA allows for a numerical solution of ground state and response properties with guaranteed accuracy and speed. Recent results , demonstrate that for large molecules the MRA approach can be faster than Gaussian bases beyond low precision. Several previous studies have employed MRA to provide reference-quality quantum chemistry data including evaluation of the aug-pc4 basis set for computation of DFT static polarizabilities on a set of 124 open and closed-shell systems. …”
Section: Introductionmentioning
confidence: 99%